2004
DOI: 10.1353/hpu.2004.0050
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of Hospital-Based Pediatric Care Across Diverse Ethnicities: The Case of Pneumonia

Abstract: Few studies have evaluated racial disparities with respect to process and outcome measures for pneumonia. We evaluated disparities with respect to process measures in addition to clinical and financial outcome measures in a pediatric population from 0 to 18 years of age. The data showed that minority populations were admitted at younger ages and were more likely to be admitted through the emergency department than their white counterparts. Substantial variation exists with respect to patterns of care and outco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…Race/ethnicity was included in the final models because there seems to be variation among different racial/ethnic groups with respect to outcomes for children hospitalized with pneumonia. 30…”
Section: Independent Variablesmentioning
confidence: 99%
See 1 more Smart Citation
“…Race/ethnicity was included in the final models because there seems to be variation among different racial/ethnic groups with respect to outcomes for children hospitalized with pneumonia. 30…”
Section: Independent Variablesmentioning
confidence: 99%
“…Previous investigations have shown that substantial variation exists with respect to patterns of care for pneumonia among different racial/ethnic groups. 30 Further research should define the contribution of such variation to differences in the LOS among patients of different racial/ethnic backgrounds.…”
Section: Commentmentioning
confidence: 99%
“…11 For example, children hospitalized in rural settings have a shorter LOS for pneumonia than those hospitalized in large urban settings. 12 Children from racial/ethnic minorities tend to have higher rates of CAP-associated complications, including death.…”
mentioning
confidence: 99%
“…12 Children from racial/ethnic minorities tend to have higher rates of CAP-associated complications, including death. 11 Decades of prior studies have documented that uninsured children are less likely than insured children to make preventive care visits and obtain prescription medications, but differences in LOS or hospitalization rates between insured and uninsured children with CAP have not been studied. 6,8,13,14 Though imperfect, insurance status is 1 proxy for healthcare access, and current healthcare reform efforts aim to improve healthcare access and decrease socioeconomic gradients in health by increasing the number of insured American children.…”
mentioning
confidence: 99%
“…The Pediatric Quality Indicators H ealth care disparities that result from ethnicity or socioeconomic status are well documented in adults and children. [1][2][3][4][5][6][7][8][9][10][11][12][13][14] Such disparities are generally considered to represent quantitative or qualitative differences, or both, in the level of care given to different groups. The state of Tennessee's managed care Medicaid Program, known as TennCare, recognized the importance of primary care in helping to control health care costs, in improving overall health, and in trying to reduce published in 2006 were asthma, short-term diabetes complications, perforated appendix, gastroenteritis, and urinary tract infections.…”
mentioning
confidence: 99%